Rheological Properties and Microscopic Characterization of Delayed Decay-Modified Asphalt Based on UV Ageing - Hening Gu; Yongqiang Zhu; Yunchu Zhu; Lijing Chu; Qinyuan Peng; Qian Chen (Advances in Materials Science and Engineering)
For clarifying the applying feasibility of hindered amine light stabilizers in asphalt binder, two types of hindered amine light stabilizers were chosen as a UV ageing resistance modifier and the modified asphalt was prepared with a selected UV ageing resistance modifier. The ultraviolet aging testing method of asphalt materials was proposed for UV ageing behavior characterization. Under the condition of different frequencies, the impact of UV ageing resistance modifier on asphalt was investigated through using the frequency sweep test of DSR. Under the effect of ultraviolet aging, the variation of thermal properties of UV ageing resistance-modified asphalt was deeply analyzed by means of a temperature scanning test of DSR following the increase of temperature. The change law of the surface morphology of light stabilizer-modified asphalt was characterized by atomic force microscopy (AFM) dynamically with the UV aging time extension. The research results showed that the hindered amine light stabilizer could improve the high temperature performance of asphalt and achieve the UV aging behavior of asphalt materials effectively. Meanwhile, the corresponding reaction mechanism was explored at the microscopic level.